Proposta de um seguidor de referência microcontrolado para os reguladores de tensão das unidades geradoras hidráulicas da primeira casa de força da UHE Tucuruí - COSTA, Jefferson Souza (2018)
Considering the search for ever greater efficiency in voltage regulators of synchronous generators, this paper presents a proposal of a microcontrolled prototype that seeks to prevent undesirable terminal voltage oscillations from occurring in the generator at the time the manual voltage regulator is exchanged for an automatic and vice versa. The proposal presents a control loop that aim to track the change of the regulator reference voltage that takes control of the terminal voltage and modify the regulator variable reference in standby, so that the references applied to the two regulators will support an even terminal voltage. This allows the exchange between regulators to be made without the “unwanted” oscillations in the value of terminal voltage. Since the voltage regulators utilize different variables to control the generator excitation, the manual type controls the field current and the automatic type controls the terminal voltage directly, it became necessary to correlate these references so that the physical characteristics of the generator could be considered. For this, tests were performed on a 350MW synchronous generator of the powerhouse I of Tucuruí Hydropower Plant, Brazilian state of Pará, in order to identify its magnetization characteristic at no load and loaded condition. After ascertaining the generator magnetization characteristic, a program was written in C language, which synthesizes the control logic of the reference follower prototype. This program was developed for a specific PIC family microcontroller. Furthermore, a physical module for the prototype was designed, so that the microcontroller perform the actions necessary to monitor the variables of interest. In this work, we describe the design of software to be embedded in the microcontroller, and the prototype physical module.